Breakthrough Video Desiccant Enhanced Evaporative Air Conditioning. (United States. Department of Energy. ; distributed by the Office of Scientific and Technical Information, U.S. Department of Energy, 2012)
Desiccant; Enhanced; Evaporative; Air; Conditioner; Devap; Doe; Nrel; National; Renewable; Energy; Lab.
Published through SciTech Connect.
04/25/2012.
Kozubal, Eric; Judkoff, Ron.
Keywords: Energy Conservation, Consumption, And Utilization.; Energy Planning, Policy, And Economy.; Direct Energy Conversion.